The Notorious Mrs. Clem : Murder and Money in the Gilded Age - Gamber, Wendy, 1958- (Book collections on Project MUSE., 2016)
In September 1868, the remains of Jacob and Nancy Jane Young were found lying near the banks of Indiana's White River. Suspicion for both deaths turned to Nancy Clem, a housewife who was also one of Mr. Young's former business partners. Wendy Gamber chronicles the life and times of this charming and persuasive Gilded Age confidence woman, who became famous not only as an accused murderess but also as an itinerant peddler of patent medicine and the supposed originator of the Ponzi scheme.